Optomechanical design of the MUSE spectrograph structure - Lewis, I; Lynn, J; Yang, S; Lau, W; Davies, R (2004)
We describe some of the design work behind the structural design of the NWSE spectrograph for the VLT1. In particular we consider the limitations on the instrument layout and the effect of its mechanical and thermal properties on the overall instrument performance.